The 3D characteristics of nystagmus in posterior semicircular canal benign paroxysmal positional vertigo - Liu, Yao; Zhang, Xueqing; Deng, Qiaomei; Liu, Qiang; Wen, Chao; Wang, Wei; Chen, Taisheng (Frontiers in Neuroscience, 2022)
Abstract: Objective: The aim of this study was to observe the 3-dimensional (3D; horizontal, vertical, and torsional) characteristics of nystagmus in patients with posterior semicircular canal canalithiasis (PSC-can)–related benign paroxysmal positional vertigo (BPPV) and investigate its correlation with Ewald's. Methods: In all, 84 patients with PSC-can were enrolled. The latency, duration, direction, and intensity of nystagmus induced by the Dix-Hallpike test in the head-hanging and sitting positions were recorded using 3D video nystagmography (3D-VNG). The characteristics of the horizontal, vertical, and torsional components of nystagmus were quantitatively analyzed. Results: 3D-VNG showed that the vertical components and torsional components of left and right ear PSC-can as induced by the head-hanging position of the Dix-Hallpike test were upward, clockwise and counterclockwise, and horizontal components were mainly contralateral. The median nystagmus intensity of each of the 3 components for consecutive 5 s was 26.3°/s, 25.0°/s, and 9.2°/s. When patients were returned to the sitting position, the direction of the vertical and torsional components of nystagmus was reversed. Only 54 patients had horizontal components of nystagmus, and 32 of them remained in the same direction. The median nystagmus intensity of the 3 components for consecutive 5 s was 9.4°/s, 6.8°/s, and 4.9°/s. The ratios of the nystagmus intensity of the horizontal, vertical, and torsional components of the head-hanging position to the sitting position were close to 2.6:1, 3.3:1, and 4.8:1. The ratios of the nystagmus intensity of the horizontal to vertical component, the horizontal to torsional component, and the vertical to torsional component of the head-hanging position were close to 1:2.9, 1:2.7, and 1.1:1. The ratios of the nystagmus intensity of the horizontal to vertical component, the horizontal to torsional component, and the vertical to torsional component of the sitting position were close to 1:1.9, 1:1.4, and 1.4:1. Conclusion: There were 3 components of nystagmus induced by the Dix-Hallpike test in patients with PSC-can. The vertical component was the strongest and the horizontal component was the weakest. The 3D characteristics of nystagmus were consistent with those of physiological nystagmus associated with the same PSC with a single-factor stimulus, in accordance with Ewald’s law.